Analysis of communicable disease reports and public education through COVID-19 contact tracing - Burke, Madeline Claire (My University, 2021)
This report summarizes the Integrated Learning Experience of a public health project completed at the Cincinnati Health Department in Cincinnati, Ohio. The public health project consisted of three main areas of work: 1) monthly reporting on reportable diseases, 2) annual reporting on the 2019-2020 influenza season, and 3) contact tracing as part of the COVID-19 public health response. Eight monthly communicable disease surveillance summary data reports representing June 2020 to February 2021 were created during the field experience. Major trends included steady increases in COVID-19 cases and dramatic decreases in influenza-associated hospitalizations. An annual report for the 2019-2020 influenza season was created as well. This report includes important demographic data and identifies possible targets for future public health interventions. Contact tracing efforts were performed through a total of 75 phone calls made to persons under investigation and close contacts. Observed obstacles to the COVID-19 public health response included community knowledge discrepancies and compassion fatigue among public health professionals.
Keywords: Reportable; surveillance; Covid-19; Influenza; Investigation